2016
DOI: 10.1177/2047487316640656
|View full text |Cite
|
Sign up to set email alerts
|

Infections in early life and premature acute coronary syndrome: A case-control study

Abstract: Infections in early life may partly explain premature coronary heart disease in adulthood and may potentiate traditional cardiovascular risk factor effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
1
16
1
2
Order By: Relevance
“…Episodes of acute infections have been associated with carotid artery IMT in children, 17 whereas conflicting results on their association with the adulthood risk of cardiovascular events have been reported. 18 , 19 In the Cardiovascular Risk in Young Finns Study population, childhood infection–related hospitalizations have been associated significantly with a worse cardiovascular risk factor profile and atherosclerotic phenotype in adulthood. 20 , 21 In addition, persistent Chlamydia pneumoniae infection may play a role in early lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…Episodes of acute infections have been associated with carotid artery IMT in children, 17 whereas conflicting results on their association with the adulthood risk of cardiovascular events have been reported. 18 , 19 In the Cardiovascular Risk in Young Finns Study population, childhood infection–related hospitalizations have been associated significantly with a worse cardiovascular risk factor profile and atherosclerotic phenotype in adulthood. 20 , 21 In addition, persistent Chlamydia pneumoniae infection may play a role in early lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible confounders that may be relevant to analysis of an association between pregnancy complications and premature ACS in adult offspring. The following variables were therefore included in the regression analyses: adulthood lifestyle (current smoking status); dietary pattern (high salty food and monosodium glutamate (MSG) intake, and high fatty food intake); socioeconomic status (monthly income and college education); parental history of CVD; childhood infections, 20 21 and adulthood cardiovascular risk factors (hypertension, raised fasting plasma glucose (≥6.1 mmol/L), low-density lipoprotein (LDL)-cholesterol, high-density lipoprotein (HDL)-cholesterol and body mass index (BMI)).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we included childhood infections (yes/no) as a confounding variable, as we 20 and others 21 have reported that childhood infection is independently associated with an early CVD hospitalisation in adult life. We defined exposure to childhood infections if participants had experienced at least one severe infection during early childhood (0–5 years of age), as previously reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation and coagulative pathways are linked, and inflammation in acute infections is frequently followed by a procoagulant state, which is characterised by activation of procoagulant pathways and inhibition of anticoagulant pathways, and probably represents one of the most important mechanisms underlying infection-associated cardiovascular disease (CVD). 6 This suggests another reason to protect against infection and identifies a post-infection window of increased CVD risk which both healthcare professionals and patients should be aware of, when additional monitoring or preventive interventions may be of particular value in reducing disease burden. 1 …”
Section: Cardiovascular Risk Condition Infectionmentioning
confidence: 99%